TORREFACTION OF EMPTY FRUIT BUNCH IN BIOMASS COMBUSTION GAS - Roslan, Rabiatul Adawieah (IRC, 2016)
Torrefaction is a promising method that significantly improves on biomass properties carried out at low temperature 473-573K in inert atmosphere. The continuous supply of inert gas for torrefaction process cause poor economic feasibility that limit the commercialization for this technology. This study investigated if the flue gas from palm oil mill boiler can be utilized as a source of torrefaction for industrial purpose. The torrefaction process was conducted using vertical tubular reactor at 3 different temperatures; 473K, 523K and 573K at 30 minutes under the presence of biomass pellet combustion gas. The effects of combustion gas for torrefaction of EFB on mass and energy yield were analyzed. Torrefaction in natural combustion gas resulted in significant decrease of mass yield and moisture content (70-40% & 88.1% respectively) but increase (36.3%) in Carbon content.